The Analysis of a Distribution Route for The Logistics of The User Material Uses The Saving Matrix Method at PT. X - Tia Novianti Putri; Asep Erik Nugraha; Ade Momon. S (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
PT X Tambun Field engages in exploration and production in the upstream oil and gas sector in each mining concession area. One of the activities carried out by the company, one of the activities carried out is the transportation and distribution of raw materials. The transportation and distribution process affects the number of company expenses at PT X. For PT X, the distribution process is expected to be as effective and efficient as possible to minimize transportation costs. This study aims to reduce transportation and distribution costs in PT X. The analytical tool used is the matrix savings method. The results obtained, distribution, reduction of 48.94% distance and equipment rental costs of 43.39% for shipments from the warehouse and distance costs of 32.31% and equipment rental costs of 30.32% for delivery from PT X Tambun Field.